Les obligations du courtier d’assurance face à la pratique et à la jurisprudence : deuxième partie - Duquette, Raymond (Assurances)

(untitled) (HEC Montréal, 1987)
In our last issue, we presented the first part of an article by Mr. Raymond Duquette on the broker's liability with regard to his client. ln the second part of his study, the author discusses the broker's legal mandate when acting on behalf of the insurer. The insurer is legally bound for any act carried out by the broker within the scope of his mandate.